1989
DOI: 10.1097/00006676-198910000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Receptors for Peptides in Experimental and Human Pancreatic Cancers

Abstract: Membrane receptors for [D-Trp6]-luteinizing hormone-releasing hormone ([D-T~P~I-LH-RH), somatostatin , and epidermal growth factor (EGF) were investigated in experimental N-nitrosobis-(2-oxopropyl)-amine (BOP)-induced pancreatic cancers of hamsters and in specimens of normal human pancreas and human pancreatic cancer obtained from autopsies. Membrane receptors for [ D -T~~~I -L H -R H were absent in the pancreas of normal hamsters, but appeared after the carcinoma was induced with BOP. Binding capacity of SS-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 21 publications
(33 reference statements)
2
34
0
1
Order By: Relevance
“…The higher binding is consistent with the fact that in our work pure pancreatic cancer cell membranes were used from a cell culture line known to be responsive to EGF (10). In addition, the affinity constant was somewhat lower (i.e., binding was of higher affinity) but of a similar order as previously reported (33,34). This supports the view that the LH-RHRs investigated by us are similar to LH-RHRs reported by others.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The higher binding is consistent with the fact that in our work pure pancreatic cancer cell membranes were used from a cell culture line known to be responsive to EGF (10). In addition, the affinity constant was somewhat lower (i.e., binding was of higher affinity) but of a similar order as previously reported (33,34). This supports the view that the LH-RHRs investigated by us are similar to LH-RHRs reported by others.…”
supporting
confidence: 92%
“…The results of pretreatment with EGF are shown in Fig. 2A (33,34). The higher binding is consistent with the fact that in our work pure pancreatic cancer cell membranes were used from a cell culture line known to be responsive to EGF (10).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Ten patients had markedly significant elevation of (Fekete et al, 1989). Carcinogen induced pancreatic tumours in hamsters showed a significantly greater response to the combination of somatostatin and LHRH agonist when compared to either drug administered on its own (Szende et al, 1990a).…”
Section: Tumour Responsementioning
confidence: 99%
“…Experimental work in animals has shown that testosterone stimulates and oestrogens inhibit the growth of pre-neoplastic pancreatic foci in male and female rats (Andren-Sandberg, 1989;Scarpelli & Konishi, 1990 (Szende et al, 1991). No such binding sites were detected in normal pancreatic cells (Fekete et al, 1989 (Serrano et al, 1988 (Furr & Woodburn, 1988) and has been shown to be an effective therapy in premenopausal women with metastatic breast carcinoma and patients with prostatic carcinoma. Toxicity to goserelin is minimal and is predictable on the basis of hormonal deprivation.…”
mentioning
confidence: 99%